Factors affecting team building effectiveness in organization - Lau, Grace Mei Ing (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Nowadays, organizations had discovered that team building effectiveness is essential in increasing the performance of the organization. However, organization needs to be concern on ensuring the practice of team building effectiveness characteristics among employees for high performance. This study aimed on exploring the relationship between the five causal factors (goals, roles, process, relationship and leadership) and team building effectiveness. The research methodology used in this study is the survey method which the research instrument is the survey questionnaire. Mainly, the pilot test is conducted by randomly distributing 30 questionnaires to the employees of CMS Clinker Sdn Bhd to determine validity and reliability of the questionnaires. Subsequently, a total of 81 respondents from Batu Lintang, Petra Jaya and Padungan fire stations were used as the actual study samples for this research. The data collected from the actual study underwent pilot test once again to ensure its validity and reliability of the questionnaires. In addition, obtained data were descriptively analyzed using frequencies and percentages. Moreover, data were also inferentially analyzed using the Pearson Correlation and Multiple Regression test. The purpose of using Pearson Correlation is to measure the relationship between the five causal factors and team building effectiveness. All of the alternative hypothesis is accepted. The results and findings showed that there was significant relationship between the five causal factors with team building effectiveness. Multiple Regression test was used to identify which factor is dominant that affects team building effectiveness. It is proved that team goals is the most dominant factor which affect team building effectiveness. In addition, the outcomes of this research provides benefits to the organization and future researcher in determining five main causal factors that affects team building effectiveness and identify suitable corrective actions to enhance and improve the effectiveness of team building in the organization.